NOT QUITE RECONCILIATION - Foster, Don (PINS-Psychology in Society, 2025)
Krog, Antjie, Mpolweni, Nosisi & Ratele, Kopano (2009) There was this goat: Investigating the Truth Commission testimony of Notrose Nobomvu Konile. Pietermaritzburg: University of Kwazulu-Natal Press. ISBN 978-1-86914-166-0 pbk. Pages vii + 235. Here is yet another book reporting on events emerging from the Truth and Reconciliation Commission (TRC) in the years 1996 to 1998. It is an unusual version, which takes as its object a single case: the testimony of Mrs Notrose Konile during the second week of the TRC hearings in April 1996. Her son Zabonke was one of the Gugulethu Seven, killed by the security police in 1986. There is a problem: the testimony of Mrs K does not make sense. The original testimony of Mrs K is confusing, unbelievable, incomprehensible. She talks among other things of a goat looking up, of digging for coal, of rocks falling on her, of unknown people. This book is an attempt, by three rather different researchers, to interpret and grasp the meaning of the nonsensical text: a hermeneutical quest. There are additional texts to explore: further testimony from Mrs Konile at a TRC hearing in November 1996 and an interview conducted by all three authors with Mrs K in isiXhosa in her own home in the village of Indwe, Eastern Cape, some ten years after her official reports. Not surprisingly the matter of translation looms large in this book, as it should in multilingual South Africa. isiXhosa-scholar Mpolweni provides retranslations of the original TRC translations from isiXhosa to English and in so-doing clears up some, but by no means all, of the problems of Mrs K’s accounts. The book also gives a full chapter devoted to the issue of simultaneous translation as done by the TRC and interviews some of the official TRC translators: most insightful.